Child Support Policy across High-Income Countries: Similar Problems, Different Approaches - Hakovirta Mia; Cuesta Laura; Haapanen Mari; Meyer Daniel R. (SAGE Publications, 2025)
We provide an overview of child support policy in high-income countries, highlighting differences in institutional arrangements, the amount of child support due, and the amount of child support received. We show that the United States expects high levels of child support from nonresident parents when compared to other countries, that noncompliance is a problem across countries, and that most European countries deal with nonpayment of child support by providing guarantees of public support for children and resident parents. The guarantee schemes vary in terms of eligibility and generosity. Throughout, we find that child support policy approaches differ across countries. A key policy implication from this review is that the United States may be expecting too much child support from nonresident parents and that it could consider guaranteeing a modest amount of public support to single-parent households.